2009
DOI: 10.1097/olq.0b013e31818eb8f8
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Approaches to Partner Notification, Diagnosis, and Treatment: Perspectives of New York County Health Departments, 2007

Abstract: Further research on alternative partner intervention strategies and discussion of PDPT is necessary to develop a forward-thinking strategic plan for STD control in the state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Providers appear more ambivalent than patients toward EPT, both in US and UK studies [22,23]. A New York study reported that health department acceptance was inversely related to the availability of other resources, such as field investigation capacity [25]. One survey of obstetricians and gynecologists in Arizona found that almost one-third of respondents were reluctant to prescribe EPT because of allergy-related concerns, whereas another 11% did not prescribe EPT due to liability concerns [24].…”
Section: Uptakementioning
confidence: 99%
“…Providers appear more ambivalent than patients toward EPT, both in US and UK studies [22,23]. A New York study reported that health department acceptance was inversely related to the availability of other resources, such as field investigation capacity [25]. One survey of obstetricians and gynecologists in Arizona found that almost one-third of respondents were reluctant to prescribe EPT because of allergy-related concerns, whereas another 11% did not prescribe EPT due to liability concerns [24].…”
Section: Uptakementioning
confidence: 99%